Trade in Energy Services: GATS and India - Arpita Mukherjee; Ramneet Goswami (Indian Council for Research on International Economic Relations (ICRIER), 2009)
Energy plays a vital role in the development of any economy and given its unequal distribution trade in energy, especially fossil fuels, is an important component of international trade. In the past, due to its public good characteristics, energy-related services were mostly supplied by the government. With liberalization and globalization the sector underwent significant transformation. Many new services developed and large multinationals emerged which increased global trade in energy services. Energy services is now an important component of all trade agreements. In the above context, this paper examines India's opportunities and constraints to trade in energy services within the GATS framework. The study found that India has the capability of exporting high-skilled manpower at competitive prices but is facing various market access, discriminatory and regulatory barriers in markets of export interest. With the entry of energyproducing countries such as Saudi Arabia into the WTO, the Doha negotiations provide an important platform to offensively push for liberalization in this sector. India needs foreign investment, technical know-how and international best practices in energy. The country has progressively liberalized this sector and there are no major entry barriers. However, India has not been successful in attracting large foreign investment and technology. This is due to various domestic barriers which make it difficult to set up a competitive operation. The study lists the reform measures which will help the sector become globally competitive, protect the interests of consumers and meet the energy needs of society. Since this sector is sensitive and is closely monitored by governments across the world, government-to-government collaborations would ease the entry process for Indian companies in foreign markets, diversify our energy resource base and improve energy security.
Keywords: F13; F14; L71; L72; L94; L95; Q4; 330; GATS; Energy; Trade; India & the WTO